2018
DOI: 10.1002/ijop.12489
|View full text |Cite
|
Sign up to set email alerts
|

Social decision making mediates the association between anger and externalising problems in Chinese adolescents

Abstract: The goal of this study was to test the mediating effect of social decision making in the relations of anger and anger control to externalising and internalising problems. A sample of 174 Chinese adolescents (mean age = 15.36 years) completed self-reports of trait anger, anger control, externalising problems, internalising problems and social decision making, which was operationalized as situational judgement reflecting an individual's ability to interact effectively with parents, teachers and peers. Findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Chinese children indicated that they would be less likely to confront an aggressor than their Dutch counterparts (Novin et al, 2011). Nevertheless, Chinese adolescents were more likely to experience depressive symptoms and anxiety if they suppressed their angry feelings (Li, Hein, Ye, & Liu, in press). Considering that cultural values may probably modify these associations, a cross-cultural comparison study is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese children indicated that they would be less likely to confront an aggressor than their Dutch counterparts (Novin et al, 2011). Nevertheless, Chinese adolescents were more likely to experience depressive symptoms and anxiety if they suppressed their angry feelings (Li, Hein, Ye, & Liu, in press). Considering that cultural values may probably modify these associations, a cross-cultural comparison study is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may consider the proportionality of the samples that enable the analysis based on sociodemographic variables. It is also important to use measures complementing self-reports, such as execution tests (Li et al, 2019;Sorge et al, 2015;Yao et al, 2019), physiological, neuropsychological measures, and experiments in decision-making (van den Bos et al, 2013;van Gelder et al, 2019). Likewise, adolescent offenders' decision-making styles and the variables that affect them should be studied so that resources can be provided to foster improvements in judgment processes, well-being, mental health, and social adjustment (Fischhoff & Broomell, 2020).…”
Section: Article In Pressmentioning
confidence: 99%
“…Among other aspects, analyzing decision-making implies knowledge of neurobiological mechanisms, the role of learning and memory, and understanding the purpose and analyzing the motivations, the context, and the dynamics that lie at the bottom of each decision (Altman, 2017). Methods for the study of decision-making are complementary to each other and include physiological and neuropsychological measures (van den Bos et al, 2013), self-reports, execution tests (Li et al, 2019;Sorge et al, 2015;Yao et al, 2019), and laboratory experiments (van Gelder et al, 2019). The decision-making analysis requires differentiation between situations, the level of importance of the decision, and cultural conditions.…”
mentioning
confidence: 99%
“…As Bruch and Feinberg (2017, p. 208) state, “the JDM literature has by and large minimized the role of social context in decision processes.” A multitude of risky‐decision studies have focused on the cognitive and physiological processes involved. However, only recently has risky decision‐making research started to focus on social influences of risky decisions (e.g., Li et al, 2019; Weiss et al, 2020).…”
mentioning
confidence: 99%